Preparation of edible film from sweet potato peel polyphenols: application in fresh fruit preservation - Zhang, Zhenlin; Wang, Yanhong; Fang, Xingtang; Chen, Xi; Yin, Zhichao; Zhang, Chunlei (Frontiers in Sustainable Food Systems, 2024)
Introduction The demand for sustainable food packaging materials has led to the exploration of bioactive composite films. This study aimed to prepare and evaluate a composite film made from sweet potato peel polyphenols extract and sweet potato starch (SPS) for its potential use in food packaging. Methods The composite film was prepared by uniformly dispersing 0.4% sweet potato peel polyphenols in the SPS matrix. Physicochemical properties and functional characteristics were assessed, including mechanical properties, UV barrier, water and gas barrier properties, antioxidant activity, and antimicrobial abilities against Bacillus subtilis, Escherichia coli, and Staphylococcus aureus. The film's efficacy in food packaging was tested using fresh cherry tomatoes, stored at 4°C, to determine its impact on shelf life. Results The starch-based sweet potato peel polyphenols film demonstrated enhanced mechanical properties and excellent UV barrier properties. It showed improved water and gas barrier properties and strong antioxidant activity, with clearance rates above 90% for DPPH and ABTS radicals. The film also exhibited effective antimicrobial abilities against the tested bacteria. Food packaging experiments indicated that the film could extend the shelf life of fresh cherry tomatoes to 7 days when stored at 4°C. Discussion The results suggest that the developed composite film has significant potential as an eco-friendly food packaging material. Its multifunctional properties, including UV protection, barrier enhancement, antioxidant activity, and antimicrobial capabilities, make it a promising candidate for extending the shelf life of perishable foods. The film's performance in slowing spoilage and extending the shelf life of cherry tomatoes highlights its practical application prospects in the food industry.